Foreign Language Anxiety Reduction Methods Induce Positive Psychological Effects on Japanese Students with Social Anxiety Disorder - Nakajima, Ai (Universitas Ahmad Dahlan, 2025)
Social Anxiety Disorder students have been overlooked in the Second Language Acquisition (SLA) domain. This study addresses this gap by focusing on them and examining the psychological effects engendered by Foreign Language Anxiety Reduction Methods. Using the Japanese version Liebowitz Social Anxiety Scale to measure Social Anxiety Disorder levels, 114 students were categorized into four levels. They participated in a four-month English course incorporating Foreign Language Anxiety Reduction Methods. Questionnaires were conducted thrice— 1st week, 7th week, and 15th week to assess students’ emotional changes. Results revealed that social anxiety manifested particularly in conjunction with communication apprehension within Foreign Language Anxiety. This response was characteristic of Social Anxiety—the fear of negative evaluation by others. Foreign Language Anxiety Reduction Methods mitigated anxieties. The most effective approach was teacher-centered affirmative support. Furthermore, the anxiety reduction order was distinctive, Social Anxiety diminishing first, followed by Foreign Language Anxiety. Additionally, anxiety alleviation increased motivation. These findings enhance our understanding of SAD learners and inform instructional practices in the Second Language Acquisition domain.